Nam Theun 2 Hydropower Project and Hydropower Development in Laos - Phomsoupha, Xaypaseuth (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Hydropower development and exporting electricity to neighboring countries is a success story in Laos. Several projects are under construction and some projects are already exporting electricity. The Nam Theun 2 Hydro-power Project (1000MW+86MW) started commercial operation on 15 March 2010. This project is exporting electricity to Thailand which is part of the MOU signed between Governments of Thailand and Laos for exporting 7000 MW to Thailand. In almost all projects, the Govt. of Laos is also a share holder. Key words: Hydropower development; Cross border electricity export; Nam Theun 2 Hydropower Project; Laos DOI: 10.3126/hn.v7i0.4227 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 14-16 Uploaded date: 31 January, 2011